First report of Rhodnius montenegrensis (Hemiptera, Reduviidae, Triatominae) in the State of Acre, Brazil - Dionatas Ulises de Oliveira Meneguetti; Simone Delgado Tojal; Pedro Raimundo Mathias de Miranda; João Aristeu da Rosa; Luis Marcelo Aranha Camargo (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
INTRODUCTION: This paper reports, for the first time, the presence of Rhodnius montenegrensis in the State of Acre, Brazil. METHODS: Two female R. montenegrensis were collected in a dwelling in the rural area of Rio Branco, Acre, Brazil. RESULTS: The occurrence of this species was confirmed, and the number of Triatominae species in the State of Acre increased from four to five. CONCLUSIONS: Further studies should be performed to reach a clearer understanding of the ecology of this arthropod, its possible role in transmitting Chagas' disease and rangeliosis, and its current geographical distribution in the region.